The constraints to good child care practices in Accra: implications for programs - Armar-Klemesu, Margaret; Ruel, Marie T.; Maxwell, Daniel G.; Levin, Carol E.; Morris, Saul Sutkover (International Food Policy Research Institute, 2000)
Life in urban areas presents special challenges for maternal child care practices. Data from a representative survey of households with children less than 3 years of age in Accra were used to test a number of hypothesized constraints to child care, including various maternal (education, employment, marital status, age, health, ethnic group, migration status) and household-level factors (income, calorie availability, quality of housing and asset ownership, availability of services, household size, and crowding). An age-specific child care index was created using recall data on maternal child feeding practices and use of preventive health services. A hygiene index was created from spot check observations of proxies of hygiene behaviors. Multivariate analyses showed that maternal schooling was the most consistent constraint to both the care and the hygiene index. None of the household-level characteristics were associated with the care index, but better housing quality and access to garbage collection services were associated with better hygiene. Female head of household and larger family size were associated with poorer hygiene. The programmatic implications of these findings for nutrition education and behavior change interventions in Accra are discussed. The focus is on using the information to target the right practices to be modified as well as the main constraints to their adoption.